A critical study of Hallaq’s “Theory of Variation of Islamic law” - Abdul Basit; Dr. Muhammad Touseef; Zobia Parveen; Hafiz Muhammad Hassaan Saeed; Muhammad Umair Raouf; Dr. Hafiz Abdul Manan Zahidi (Al-Qanṭara, 2023)
Much has been written in each part of the world about Islamic law. In our times "Modern State" based on "Modern Law" is a big challenge for Muslim communities to adapt "Modern Law" as "Islamic Law" Or to use sources of "Modern Law" as "Sources of Islamic law. From historical development, society is under variation so law is also variable thing and it is an acceptable and recommended concept in modern world.in the modern scenario it's a big challenge for Muslims to deal with this concept of variation in law and its sources. From Islamic history variation in Islamic law is adjustable with concept of Ijtihad.in this sense its acceptable concept to modify Islamic law according to need of society in accordance with modern law. Then why modifications in Islamic law in accordance with modern law are opposed in Muslim communities or states? What is difference between concept of variation in Islamic law developed by Muslim traditional communities and modern western scholars?